Upaya Meminimalisir Angka Peningkatan Pernikahan Usia Dini Melalui Koordinasi Kelembagaan Pemerintah Kota Banjar Tahun 2023 - Jernih Fuji Koesnead; Aan Anwar Sihabudin; Budi Setiadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The causes of early marriage are influenced by various factors, including their low level of education which influences their mindset in understanding and comprehending the nature and purpose of marriage as well as parents who are afraid that their children will become spinsters. Research Object: 7 people were informants (primary data) in this research. Objective: This research aims to determine the institutional coordination of the Banjar City government in minimizing the increase in the number of early marriages in 2023.